Ocean Yearbook Online - Ocean Yearbook Online (Brill, 2026)
Devoted to assessing the state of ocean and coastal governance, knowledge, and management, the Ocean Yearbook Online provides information in one convenient resource. Articles provide multidisciplinary expert perspectives on contemporary issues. Each new volume draws on policy studies, international relations, international and comparative law, management, marine sciences, economics, and social sciences.
FI 0.12
Q4
Keywords: Law of the sea; Oceanografía; Acuerdos transformativos; Transformative agreements; Gestión oceánica y costera; Ciencias marinas